The organometallic chemistry of the transition metals - Crabtree, Robert H., 1948- (Hoboken, New Jersey : Wiley, 2014)
Fully updated and expanded to reflect recent advances, the sixth edition of this bestselling text provides students and professional chemists with a comprehensive introduction to the principles and general properties of organometallic compounds, as well as including practical information on reaction mechanisms and detailed descriptions of contemporary applications. Increased focus is given to organic synthesis applications, nanoparticle science, and green chemistry. This edition features: New sections on Multifunctional Ligands, Oxidation Catalysis, and Green ChemistryExpanded discussion on to.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Organometallic chemistry; Organotransition metal compounds; SCIENCE -- Chemistry -- Organic; Organometallic chemistry; Organotransition metal compounds; Electronic books; Electronic books